Method for producing iron phosphate using iron phosphorus slag, iron phosphate and its application

A method for producing high-purity iron phosphate from waste lithium iron phosphate slag through alkali treatment, acid-based dealumination, and impurity removal processes addresses high impurity content, achieving efficient and cost-effective resource utilization for lithium ion batteries.

JP2024547058AActive Publication Date: 2024-12-26HUBEI HONGRUN HIGH-TECH NEW MATERIALS CO LTD

Patent Information

Application Number
JP2024537008
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-06-27
Filing Date
2022-12-09
Publication Date
2024-12-26
Estimated Expiration
2042-12-09

AI Technical Summary

Technical Problem

Existing methods for recovering lithium iron phosphate waste struggle with high metal impurity content, particularly aluminum, titanium, and copper, leading to low-value utilization of iron phosphate slag, resulting in resource waste.

Method used

A method involving alkali treatment, acid-based dealumination, decarbonization, and titanation/copper removal processes to produce high-purity iron phosphate from waste lithium iron phosphate slag, utilizing steps (a) to (d) to separate and remove impurities effectively.

Benefits of technology

The method achieves low-cost, high-purity iron phosphate production, suitable for lithium ion batteries, with impurity levels below 100 ppm, reducing resource waste and enhancing battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024547058000001_ABST
    Figure 2024547058000001_ABST
Patent Text Reader

Abstract

The method for producing iron phosphate using iron phosphorus slag includes the steps of adding iron phosphorus slag to an alkaline solution, reacting the slag, and then performing solid-liquid separation to obtain a filter cake and a first filtrate containing metaaluminate ions and phosphate ions; adding an acid solution to the first filtrate to perform a dealumination reaction, and then performing solid-liquid separation to obtain a second filtrate containing phosphate ions; mixing the filter cake and the acid solution to perform a decarbonization reaction, and then performing solid-liquid separation to obtain a third filtrate containing iron ions, titanium ions and copper ions; adding metallic iron to the third filtrate to perform a detitanization and decopperization reaction, and then performing solid-liquid separation to obtain a fourth filtrate containing ferrous ions; and mixing an oxidizing agent, the second filtrate, and the fourth filtrate to react with each other, and then performing solid-liquid separation and sintering in this order to obtain iron phosphate.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority to a Chinese patent application filed on June 27, 2022, bearing application number 202210735393.5 and entitled "Method for producing iron phosphate using iron phosphorus slag, iron phosphate and its application," the disclosure of which is incorporated herein by reference.

[0002] The present invention relates to the technical field of lithium ion batteries, and more particularly to a method for producing iron phosphate using iron phosphorus slag, iron phosphate and its applications. [Background technology]

[0003] In recent years, with the development of new energy vehicles in China, the sales volume of power batteries, which are the core components of new energy vehicles, has increased year by year, but a large amount of waste batteries has also been generated. Traditional physical methods have difficulty in restoring the performance of lithium iron phosphate waste. The recovery of lithium iron phosphate batteries usually prioritizes the extraction of lithium element with high added value, and the large amount of iron phosphate slag generated after lithium extraction is generally treated with low value as industrial waste or filler for cement plants. The fact that the large amount of iron and phosphorus elements contained in iron phosphate slag are not effectively recovered and utilized causes huge resource waste. Therefore, developing a recovery and production method for iron phosphate with a simple process, easy to control, and environmentally friendly is particularly important for the construction of a green industrial chain.

[0004] The high content of metal impurities is currently the main problem in the recovery and utilization of ferrophosphorus slag, and traditional recovery methods are mainly concerned with removing aluminum impurities, and little with removing other impurity elements, such as titanium, copper, etc.

[0005] For example, patent document CN113753873A discloses a method for producing petal-shaped iron phosphate with low aluminum impurities using waste iron phosphorus slag, selectively removing aluminum based on the difference in solubility between the aluminum impurities in iron phosphorus slag and iron phosphate, and the method is an acidic system that only removes aluminum impurities and cannot remove titanium impurities or copper impurities in iron phosphorus slag. The produced iron phosphate product contains a large amount of titanium impurities and copper impurities, which has certain limitations.

[0006] Therefore, how to thoroughly remove impurity metal elements from iron phosphate slag at low cost to produce iron phosphate with low impurity content is of great significance.

[0007] In view of this, the present invention is proposed. Summary of the Invention [Problem to be solved by the invention]

[0008] A first object of the present invention is to provide a method for producing iron phosphate using iron phosphorus slag, which can effectively remove aluminum impurities, carbon impurities, titanium impurities and copper impurities in iron phosphorus slag, and the impurity content of the produced iron phosphate is low, and further, the method has the advantages of simple process, easy control and low cost.

[0009] A second object of the present invention is to provide high quality iron phosphate having a low content of impurities.

[0010] A third object of the present invention is to provide a positive electrode material for a lithium ion battery. [Means for solving the problem]

[0011] In order to achieve the above object of the present invention, the following technical means are used.

[0012] The present invention provides a method for producing (anhydrous) iron phosphate using iron phosphorus slag, comprising the following steps (a) to (d):

[0013] In step (a), the ferrophosphorus slag is added to an alkaline solution (an aqueous solution containing an alkali), and aluminum hydroxide and metallic aluminum (simple aluminum) in the ferrophosphorus slag are dissolved by reacting with the alkaline solution, and iron in the ferrophosphorus slag is reacted with hydroxide ions in the alkaline solution to produce an iron hydroxide precipitate. After the reaction is completed, solid-liquid separation is performed to obtain a filter cake and a first filtrate containing metaaluminate ions and phosphate ions (in this invention, "contain" means "include" and may contain other ions or components).

[0014] Here, the iron phosphorus slag includes waste material obtained after extracting lithium (extracting lithium element) from discarded lithium iron phosphate batteries, and the iron phosphorus slag includes iron phosphate, aluminum hydroxide, metallic aluminum, carbon, metallic copper, copper oxide, and titanium oxide.

[0015] Here, the main components of the filter cake include iron hydroxide, carbon (element), metallic copper (element copper), copper oxide, and titanium oxide.

[0016] The anions in the first filtrate include metaaluminate, phosphate and hydroxide.

[0017] The reaction principle in step (a) is as follows. FePO 4 +3OH - →Fe(OH) 3 +PO 4 3- ; Al(OH) 3 +OH - →AlO 2 - +2H 2 O; 2Al+2H 2 O+2OH - →2AlO2 - +3H 2 ↑.

[0018] This step can separate the phosphorus and aluminum elements from the iron, titanium, copper and carbon elements in the ferrophosphorus slag, facilitating the subsequent removal of impurities and the synthesis reaction of ferrophosphate.

[0019] Then, an acid solution (an aqueous solution containing an acid) is added to the first filtrate containing metaaluminate ions and phosphate ions to carry out a dealumination reaction, in which the metaaluminate ions in the first filtrate react with the hydrogen ions in the acid solution to produce an aluminum hydroxide precipitate. After the dealumination reaction is completed, solid-liquid separation is performed to obtain a second filtrate containing phosphate ions, which is then prepared for use.

[0020] In this step, the second filtrate containing phosphate ions is obtained, and aluminum hydroxide filter cake is also obtained. In this step, aluminum impurities are precipitated as aluminum hydroxide, and the purpose of dealumination is achieved after solid-liquid separation.

[0021] The reaction principle in this step is H 2 O+AlO 2 - +H + →Al(OH) 3 Includes the following.

[0022] The anions in the second filtrate are primarily phosphate ions.

[0023] In step (b), the filter cake obtained in step (a) is mixed with an acid solution to carry out a decarbonization reaction, and then solid-liquid separation is performed to obtain a carbon cake (the main components of which are elemental carbon and elemental copper) and a third filtrate containing iron ions, titanium ions and copper ions.

[0024] Here, the iron hydroxide precipitate and copper oxide in the filter cake react with the acid to dissolve, generating iron ions and copper ions. At the same time, part of the titanium oxide in the filter cake dissolves in the acid solution, while the other part (undissolved titanium oxide) precipitates together with elemental carbon and elemental copper, so that separation of carbon, iron, and titanium can be achieved after solid-liquid separation.

[0025] In step (c), metallic iron (iron element, e.g., iron powder or iron shell) is added to the third filtrate containing iron ions, titanium ions, and copper ions obtained in step (b) to carry out a detitanization and decopperization reaction, followed by solid-liquid separation to obtain a fourth filtrate containing ferrous ions.

[0026] Here, the fourth filtrate containing ferrous ions is obtained, and the main components are metallic copper (copper alone) and metatitanic acid (TiO(OH) 2 A mixed cake, which is titanium dioxide (also called hydrated titanium dioxide), is also obtained.

[0027] The reaction principle in step (c) includes the following: Fe+Cu 2+ →Cu+Fe 2+ ; Fe+2H + →Fe 2+ +H 2 ↑; Ti 4+ +3H 2 O → TiO(OH) 2 +4H + .

[0028] In step (c), metallic iron is added to neutralize the residual acid in the third filtrate, thereby increasing the pH value of the third filtrate and increasing the content of ferrous ions in the third filtrate. In addition, titanium impurities are hydrolyzed to form metatitanic acid precipitates to achieve the purpose of removing titanium, and copper impurities are subjected to a substitution reaction to achieve the purpose of removing copper. Therefore, the solid-liquid separation in step (c) can separate the copper and titanium impurities from the iron.

[0029] In some specific embodiments of the present invention, in step (c), excess metallic iron may be added to ensure complete reaction, and the mixed cake further contains a small amount of metallic iron.

[0030] In step (d), an oxidizing agent is mixed with the second filtrate containing the phosphate ions obtained in step (a) and the fourth filtrate containing the ferrous ions obtained in step (c) to cause a reaction. After the reaction is completed, solid-liquid separation and sintering are carried out in this order to obtain iron phosphate.

[0031] Here, the iron phosphate is anhydrous iron phosphate.

[0032] The reaction principle in step (d) includes the following: When ferrous ions react with an oxidizing agent to produce ferric ions, and the oxidizing agent is hydrogen peroxide, the reaction is: 2Fe 2+ +H 2 O 2 +2H + →2Fe 3+ +2H 2 O; Fe 3+ +PO 4 3- +2H 2 O→FePO 4 2H 2 O; FePO 4 2H 2 O→FePO 4 +2H 2 It is O.

[0033] The present invention uses waste ferrophosphorus slag as raw material, and has the advantages of low cost, avoiding resource waste, and being environmentally friendly.

[0034] In addition, the method can effectively remove aluminum impurities, carbon impurities, titanium impurities and copper impurities in the iron phosphorus slag. After dealuminization, decarbonization, detitanium and decopper, the iron phosphate produced has a low impurity content, high quality and high added value, and can be used as a precursor of lithium iron phosphate for power generation.

[0035] Preferably, in step (a), the mass ratio of the ferrophosphorus slag to the alkaline liquid is 1:3-10, including, but not limited to, any one of the following points or any two of the following range values: 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, more preferably 1:4-6.

[0036] Preferably, in step (a), the mass fraction of the alkaline liquid (the mass fraction of the alkali in the aqueous solution containing the alkali) is 8% to 20%, including, but not limited to, any one of the following point values ​​or any two range values: 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, and 19%.

[0037] Preferably, in step (a), the alkaline liquid comprises a sodium hydroxide solution and / or a potassium hydroxide solution.

[0038] Preferably, in step (a), during the reaction of the ferrophosphorus slag with the alkaline liquid, the temperature of the mixture is 30-80°C, including but not limited to any one of the following points or any two range values: 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 78°C, and the reaction time is 1-3 hours, including but not limited to any one of the following points or any two range values: 1.5 hours, 2 hours, 2.5 hours.

[0039] Use of the above parameters is advantageous in promoting the dissolution of aluminum hydroxide and metallic aluminum, and is advantageous in improving the dealumination efficiency.

[0040] Preferably, in step (a), the acid used in the acid solution comprises at least one of sulfuric acid, hydrochloric acid, phosphoric acid and nitric acid, more preferably phosphoric acid.

[0041] Here, the phosphate ions in the phosphoric acid can be used as a raw material for the subsequent synthesis reaction of iron phosphate.

[0042] Preferably, in step (a), the mass fraction of the acid solution (the mass fraction of the acid in the aqueous solution containing the acid) is 30% to 85%, including, but not limited to, any one of the following point values ​​or any two range values: 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%.

[0043] Preferably, in step (a), the acid solution is added until the pH of the mixture is between 5.0 and 7.5, including but not limited to any one of the following spot values ​​or range values ​​between any two of 5.2, 5.5, 5.8, 6.0, 6.3, 6.5, 6.8, 7.0, 7.2, more preferably 6.8 to 7.1.

[0044] In some specific embodiments of the present invention, in step (a), the temperature of the mixture during the dealumination reaction is 15 to 80°C, including, but not limited to, any one of the following points or any two of the range values: 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, and 75°C.

[0045] The use of the above parameters is advantageous in promoting the precipitation of aluminum hydroxide, improving the dealumination effect.

[0046] Preferably, in step (b), the molar ratio of iron element in the filter cake to hydrogen ion in the acid solution is 1:3.1-4, including but not limited to any one of the following points or any two range values: 1:3.2, 1:3.3, 1:3.4, 1:3.5, 1:3.6, 1:3.7, 1:3.8, 1:3.9.

[0047] Preferably, in step (b), the acid comprises at least one of sulfuric acid, hydrochloric acid, nitric acid and phosphoric acid, more preferably at least one of sulfuric acid, hydrochloric acid and nitric acid, which are the three acids that are lower in cost.

[0048] Preferably, in step (b), the molar concentration of the acid solution (the molar concentration of the acid in the aqueous solution containing the acid) is 1 to 3 mol / kg, including, but not limited to, any one of the following point values ​​or any two range values: 1.3 mol / kg, 1.5 mol / kg, 1.8 mol / kg, 2.0 mol / kg, 2.3 mol / kg, 2.5 mol / kg, 2.8 mol / kg, 3 mol / kg.

[0049] Preferably, in step (b), the temperature of the mixture during the decarbonization reaction is 60 to 80°C, including, but not limited to, any one of the following points or any two of the following range values: 63°C, 65°C, 68°C, 70°C, 73°C, 75°C, 78°C.

[0050] Preferably, in step (b), the decarbonization reaction time is 1 to 3 hours, including, but not limited to, any one of the following points or any two of the following range values: 1.5 hours, 2 hours, 2.5 hours, and 3 hours, and more preferably, 1 to 1.5 hours.

[0051] The use of the above parameters is advantageous for separating carbon from iron, titanium and copper.

[0052] Preferably, in step (c), the temperature of the mixture during the detitanization and decopperization reaction is 75 to 85°C, including, but not limited to, any one of the following points or a range between any two of 76°C, 77°C, 78°C, 79°C, 80°C, 82°C, 83°C, and 84°C.

[0053] Preferably, in step (c), the solid-liquid separation is carried out when the pH of the mixture during the titanation and copper removal reaction reaches 2 to 4.2, which includes, but is not limited to, any one of the following points or a range between any two of 2.3, 2.5, 2.8, 3.0, 3.2, 3.5, 3.7, and 3.9.

[0054] The use of the above parameters is advantageous in achieving separation of copper and titanium impurities from iron.

[0055] Preferably, in step (d), the oxidizing agent comprises at least one of hydrogen peroxide, sodium peroxide, potassium peroxide, sodium persulfate, ammonium persulfate, and potassium persulfate, and is more preferably hydrogen peroxide.

[0056] Preferably, in step (d), the molar ratio of ferrous ion in the fourth filtrate to hydrogen peroxide in the hydrogen peroxide solution is 1:0.55-0.75, including but not limited to any one of the following points or any two range values: 1:0.58, 1:0.6, 1:0.62, 1:0.65, 1:0.68, 1:0.7, 1:0.73. By using this molar ratio, ferrous ion can be completely oxidized and costs can be saved.

[0057] Preferably, in step (d), the molar ratio of phosphate ions in the second filtrate to ferrous ions in the fourth filtrate is 1.05 to 1.5:1, including, but not limited to, any one of the following point values ​​or range values ​​between any two of 1.1:1, 1.15:1, 1.2:1, 1.25:1, 1.3:1, 1.35:1, 1.4:1, 1.45:1.

[0058] Preferably, in step (d), the temperature of the mixture during the reaction is 80 to 95°C, including, but not limited to, any one of the following points or any two of the range values: 83°C, 85°C, 88°C, 90°C, and 93°C.

[0059] The use of the above molar ratio and reaction temperature is advantageous in obtaining iron phosphate of higher quality.

[0060] Preferably, in step (d), the reaction time is 2 to 6 hours, including but not limited to any one of the following points or any two of the range values: 2 hours, 3 hours, 4 hours, 5 hours, 6 hours.

[0061] Preferably, in step (d), the sintering temperature is 550 to 700°C, including, but not limited to, any one of the following points or any two of the following range values: 570°C, 590°C, 600°C, 620°C, 650°C, 680°C, 700°C.

[0062] Here, the purpose of sintering is to remove the water of crystallization in the iron phosphate. Before sintering, the obtained product is iron phosphate dihydrate, which is dehydrated at high temperature by sintering to obtain anhydrous iron phosphate.

[0063] In some specific embodiments of the present invention, after the solid-liquid separation and before the sintering, the method further comprises washing and drying the solid material after the solid-liquid separation.

[0064] The present invention further provides iron phosphate produced by the method for producing iron phosphate using the above-mentioned iron phosphorus slag.

[0065] The iron phosphate has a low impurity content, high quality and low cost.

[0066] Preferably, the iron / phosphorus ratio of the iron phosphate is 0.96 to 0.98, including, but not limited to, any one of the following point values ​​or any range value between any two of 0.963, 0.964, 0.965, 0.968, 0.97, 0.972, 0.974, 0.975, 0.978.

[0067] The present invention further provides a positive electrode material for a lithium ion battery containing the above iron phosphate.

[0068] By using the above iron phosphate, the cost can be controlled to be low, and the iron phosphate with low impurity content is advantageous for improving the electrochemical performance of lithium ion batteries. Effect of the Invention

[0069] Compared with the prior art, the advantages of the present invention are as follows: (1) The method for producing iron phosphate using iron phosphorus slag according to the present invention can effectively remove aluminum impurities, carbon impurities, titanium impurities and copper impurities in iron phosphorus slag through a series of impurity removal operations, and the impurity content of the produced iron phosphate is low. (2) The method for producing iron phosphate using iron phosphate slag according to the present invention uses discarded iron phosphate slag as a raw material, and has the advantages of low cost, avoiding resource waste, and being environmentally friendly. [Brief description of the drawings]

[0070] In order to more clearly describe the specific embodiments of the present invention or the technical solutions in the prior art, the drawings necessary for describing the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention, and those skilled in the art can further obtain other drawings based on these drawings without creative labor. [Figure 1] 1 is an XRD chart of anhydrous iron phosphate according to Example 1 of the present invention. [Diagram 2] FIG. 2 is a 50,000-times magnified SEM image of anhydrous iron phosphate according to Example 1 of the present invention. [Diagram 3] FIG. 2 is a 200,000-times magnified SEM image of anhydrous iron phosphate according to Example 1 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0071] The technical means of the present invention will be described below clearly and completely with reference to the drawings and specific embodiments. Those skilled in the art should understand that the examples described below are only some of the examples of the present invention, not all of the examples, and are only for illustrating the present invention and do not limit the scope of the present invention. Based on the examples of the present invention, all other examples obtained by those skilled in the art without creative labor are within the scope of protection of the present invention. In the examples, specific conditions are not specified, but are in accordance with normal conditions or conditions proposed by the manufacturer. In the examples, the manufacturers of the reagents or instruments used are not specified, and are all normal products available on the market.

[0072] The iron phosphorus slag in the following examples and comparative examples of the present invention is a waste material obtained after extracting lithium from discarded lithium iron phosphate batteries. The main components of the iron phosphorus slag include iron phosphate, aluminum hydroxide, metallic aluminum, carbon, metallic copper, copper oxide, and titanium oxide. Example 1

[0073] The method for producing iron phosphate using iron phosphorus slag according to the present embodiment includes the following steps (1) to (5).

[0074] In step (1), 100 g of ferrophosphorus slag is taken and put into a NaOH solution with a mass fraction of 14%, slurried and dispersed, and reacted at a reaction temperature of 50° C., and the mass ratio of the ferrophosphorus slag to the NaOH solution is 1:3. After reacting for 2 hours, solid-liquid separation is performed to obtain a filter cake and a first filtrate containing metaaluminate ions and phosphate ions.

[0075] In step (2), phosphoric acid having a mass fraction of 85% was added to the first filtrate containing metaaluminate ions and phosphate ions obtained in step (1), the pH value of the mixture was adjusted to 7.0±0.1, and a dealumination reaction was carried out. After completion of the reaction, solid-liquid separation was performed to obtain a filter cake of aluminum hydroxide and a second filtrate containing phosphate ions (to be prepared for use).

[0076] In step (3), the filter cake obtained in step (1) was added to and dissolved in a sulfuric acid solution having a molar concentration of 3 mol / kg to carry out a decarbonization reaction. The molar ratio of the iron element in the filter cake to the hydrogen ion in the sulfuric acid solution was 1:3.6, and the reaction temperature was 80°C. After the reaction was carried out for 1 hour, solid-liquid separation was performed to obtain a carbon cake and a third filtrate containing iron ions, titanium ions and copper ions.

[0077] In step (4), iron powder was added to the third filtrate containing iron ions, titanium ions, and copper ions obtained in step (3) to carry out a detitanization and decopperization reaction. The reaction temperature was 80°C and the reaction was continued until the pH value of the mixture reached 4.0±0.2. Solid-liquid separation was then performed to obtain a fourth filtrate containing ferrous ions and a mixed filter cake containing metallic copper and metatitanic acid.

[0078] In step (5), the hydrogen peroxide solution and the second filtrate containing phosphate ions obtained in step (2) were uniformly mixed to prepare a phosphate solution, and then the phosphate solution was added dropwise to the fourth filtrate containing ferrous ions obtained in step (4) to carry out a reaction to synthesize iron phosphate, in which the molar ratio of the phosphate ions in the second filtrate to the ferrous ions in the fourth filtrate was 1.1:1, and the molar ratio of the ferrous ions in the fourth filtrate to the hydrogen peroxide in the hydrogen peroxide solution was 1:0.6, the reaction temperature was 95°C, and the reaction was carried out for 3 hours, followed by solid-liquid separation, and then washing, drying, and sintering (sintering temperature was 600°C) were carried out in that order to obtain anhydrous iron phosphate with an iron / phosphorus ratio of 0.9637.

[0079] The detection results of the contents of phosphorus and aluminum elements in the first filtrate containing metaaluminate ions and phosphate ions obtained in step (1) (i.e., before dealumination) and the second filtrate containing phosphate ions obtained in step (2) (i.e., after dealumination) are shown in Table 1 below.

[0080] Table 1 Comparison of phosphorus and aluminum content before and after dealumination [Table 1]

[0081] The detection results of the contents of copper and titanium elements in the third filtrate containing iron ions, titanium ions, and copper ions obtained in step (3) (i.e., before copper and titanium are removed) and the fourth filtrate containing ferrous ions obtained in step (4) (i.e., after copper and titanium are removed) are shown in Table 2 below.

[0082] Table 2 Comparison of copper and titanium element contents before and after copper and titanium removal [Table 2]

[0083] The results of detection of the content of impurity elements (metal elements) in the anhydrous iron phosphate obtained in step (5) are shown in Table 3 below.

[0084] Table 3 Content of impurity elements in anhydrous iron phosphate [Table 3]

[0085] As can be seen from the detection results in Table 3, the contents of all impurity elements in the anhydrous iron phosphate are all less than 100 ppm.

[0086] The anhydrous iron phosphate obtained in step (5) was subjected to XRD detection, and the results are shown in FIG. 1. As can be seen from FIG. 1, the anhydrous iron phosphate obtained in the present invention is FePO4 (JCPDF card number: 29-0715). According to the types and contents of the detected impurity elements in Table 3, the purity of the iron phosphate produced in this embodiment is 99.74%, and the total content of impurities is 0.26%.

[0087] The anhydrous iron phosphate obtained in step (5) was subjected to SEM detection, and the results are shown in Figures 2 and 3. Figure 2 is an SEM image of iron phosphate enlarged 50,000 times, and Figure 3 is an SEM image of iron phosphate enlarged 200,000 times, which show that the microstructure of the anhydrous iron phosphate obtained in the present invention is a nanosheet structure, and the particle size of the primary particles is about 400 nm. Example 2

[0088] The method for producing iron phosphate using iron phosphorus slag according to the present embodiment includes the following steps (1) to (5).

[0089] In step (1), 100 g of ferrophosphorus slag is taken and put into a KOH solution with a mass fraction of 8%, slurried and dispersed, and reacted at a reaction temperature of 35°C, and the mass ratio of the ferrophosphorus slag to the KOH solution is 1:10. After reacting for 3 hours, solid-liquid separation is performed to obtain a filter cake and a first filtrate containing metaaluminate ions and phosphate ions.

[0090] In step (2), sulfuric acid having a mass fraction of 40% was added to the first filtrate containing metaaluminate ions and phosphate ions obtained in step (1) to adjust the pH value of the mixture to 6.5±0.1, and a dealumination reaction was carried out. After completion of the reaction, solid-liquid separation was performed to obtain a filter cake of aluminum hydroxide and a second filtrate containing phosphate ions (to be prepared for use).

[0091] In step (3), the filter cake obtained in step (1) was added to and dissolved in a sulfuric acid solution having a molar concentration of 1 mol / kg to carry out a decarbonization reaction. The molar ratio of the iron element in the filter cake to the hydrogen ion in the sulfuric acid solution was 1:3.1, and the reaction temperature was 60°C. After the reaction was carried out for 3 hours, solid-liquid separation was performed to obtain a carbon cake and a third filtrate containing iron ions, titanium ions and copper ions.

[0092] In step (4), iron powder was added to the third filtrate containing iron ions, titanium ions, and copper ions obtained in step (3) to carry out a detitanization and decopperization reaction. The reaction temperature was 75°C and the reaction was continued until the pH value of the mixture reached 2.5±0.2. Solid-liquid separation was then performed to obtain a fourth filtrate containing ferrous ions and a mixed filter cake containing metallic copper and metatitanic acid.

[0093] In step (5), the hydrogen peroxide solution and the second filtrate containing phosphate ions obtained in step (2) were uniformly mixed to prepare a phosphate solution, and the phosphate solution was then dropped into the fourth filtrate containing ferrous ions obtained in step (4) to carry out a reaction to synthesize iron phosphate, in which the molar ratio of the phosphate ions in the second filtrate to the ferrous ions in the fourth filtrate was 1.5:1, and the molar ratio of the ferrous ions in the fourth filtrate to the hydrogen peroxide in the hydrogen peroxide solution was 1:0.55, the reaction temperature was 80°C, and the reaction was carried out for 4 hours, followed by solid-liquid separation, and then washing, drying, and sintering (sintering temperature was 700°C) were carried out in that order to obtain anhydrous iron phosphate with an iron / phosphorus ratio of 0.9701.

[0094] Through detection and calculation, the Al removal rate in step (2) of this example is 96.01%, the Cu removal rate in step (4) is 99.95%, the Ti removal rate in step (4) is 99.02%, and the contents of all impurity elements in the anhydrous iron phosphate obtained in step (5) are less than 100 ppm. Example 3

[0095] The method for producing iron phosphate using iron phosphorus slag according to the present embodiment includes the following steps (1) to (5).

[0096] In step (1), 100 g of ferrophosphorus slag is taken and put into a NaOH solution with a mass fraction of 20%, slurried and dispersed, and reacted at a reaction temperature of 80° C. and a mass ratio of the ferrophosphorus slag to the NaOH solution of 1:5. After reacting for 1 hour, solid-liquid separation is performed to obtain a filter cake and a first filtrate containing metaaluminate ions and phosphate ions.

[0097] In step (2), hydrochloric acid having a mass fraction of 60% was added to the first filtrate containing metaaluminate ions and phosphate ions obtained in step (1) to adjust the pH value of the mixture to 5.5±0.1, and a dealumination reaction was carried out. After completion of the reaction, solid-liquid separation was performed to obtain a filter cake of aluminum hydroxide and a second filtrate containing phosphate ions (to be prepared for use).

[0098] In step (3), the filter cake obtained in step (1) was added to and dissolved in a nitric acid solution having a molar concentration of 2 mol / kg to carry out a decarbonization reaction. The molar ratio of the iron element in the filter cake to the hydrogen ion in the nitric acid solution was 1:4, and the reaction temperature was 70°C. After the reaction was carried out for 1.5 hours, solid-liquid separation was performed to obtain a carbon cake and a third filtrate containing iron ions, titanium ions and copper ions.

[0099] In step (4), iron powder was added to the third filtrate containing iron ions, titanium ions, and copper ions obtained in step (3) to carry out a detitanization and decopperization reaction. The reaction temperature was 85°C and the reaction was continued until the pH value of the mixture reached 3.0±0.2. Solid-liquid separation was then performed to obtain a fourth filtrate containing ferrous ions and a mixed filter cake containing metallic copper and metatitanic acid.

[0100] In step (5), the hydrogen peroxide solution and the second filtrate containing phosphate ions obtained in step (2) were uniformly mixed to prepare a phosphate solution, and then the phosphate solution was added dropwise to the fourth filtrate containing ferrous ions obtained in step (4) to carry out a reaction to synthesize iron phosphate, in which the molar ratio of the phosphate ions in the second filtrate to the ferrous ions in the fourth filtrate was 1.3:1, the molar ratio of the ferrous ions in the fourth filtrate to the hydrogen peroxide in the hydrogen peroxide solution was 1:0.75, the reaction temperature was 90°C, and the reaction was carried out for 4 hours, followed by solid-liquid separation, and then washing, drying, and sintering (sintering temperature: 550°C) were carried out in that order to obtain anhydrous iron phosphate with an iron / phosphorus ratio of 0.9723.

[0101] Through detection and calculation, the Al removal rate in step (2) of this example is 95.72%, the Cu removal rate in step (4) is 99.96%, the Ti removal rate in step (4) is 98.21%, and the contents of all impurity elements in the anhydrous iron phosphate obtained in step (5) are less than 100 ppm. Comparative Example 1

[0102] The method for producing iron phosphate using iron phosphorus slag according to this comparative example is almost the same as that of Example 1, except that in step (2), the pH value of the mixture is adjusted to 4.0±0.1.

[0103] Through detection and calculation, the Al removal rate in step (2) of the comparative example is 42.32%, the purity of the produced iron phosphate is 98.56%, and the total content of impurity elements is 1.44%. Comparative Example 2

[0104] The method for producing iron phosphate using iron phosphorus slag according to this comparative example is almost the same as that of Example 1, except that the reaction temperature is changed to 50° C. in step (4).

[0105] Through detection and calculation, the Cu removal rate in step (4) of the comparative example is 95.45%, the Ti removal rate is 64.20%, the purity of the produced iron phosphate is 99.45%, and the total content of impurity elements is 0.55%.

[0106] Although the present invention has been described with reference to specific embodiments, the above embodiments are merely for illustrating the technical means of the present invention and are not intended to be limiting. It should be understood that a person skilled in the art may modify the technical means described in the above embodiments or make equivalent substitutions for some or all of the technical features thereof without departing from the spirit and scope of the present invention. These modifications and substitutions do not cause the essence of the corresponding technical means to depart from the scope of the technical means of the embodiments of the present invention. Therefore, the appended claims are intended to include all substitutions and modifications that fall within the protection scope of the present invention.

Claims

1. (a) adding ferrophosphorus slag to an alkaline solution, reacting with the ferrophosphorus slag, and then performing solid-liquid separation to obtain a filter cake and a first filtrate containing metaaluminate ions and phosphate ions; adding an acid solution to the first filtrate to carry out a dealumination reaction; and performing solid-liquid separation after the dealumination reaction is completed to obtain a second filtrate containing phosphate ions; Step (b) of mixing the filter cake obtained in step (a) with an acid solution to carry out a decarbonization reaction, and then performing solid-liquid separation to obtain a carbon cake and a third filtrate containing iron ions, titanium ions and copper ions; (c) adding metallic iron to the third filtrate obtained in step (b) to carry out a detitanization and decopperization reaction, and then subjecting the resulting mixture to solid-liquid separation to obtain a fourth filtrate containing ferrous ions; and (d) mixing and reacting an oxidizing agent with the second filtrate containing phosphate ions obtained in step (a) and the fourth filtrate containing ferrous ions obtained in step (c), and after the reaction is completed, sequentially performing solid-liquid separation and sintering to obtain iron phosphate. The method for producing iron phosphate using the phosphorus iron slag, wherein the phosphorus iron slag comprises a waste material obtained after extracting lithium from discarded lithium iron phosphate batteries, and the phosphorus iron slag comprises iron phosphate, aluminum hydroxide, metallic aluminum, carbon, metallic copper, copper oxide, and titanium oxide.

2. In step (a), the mass ratio of the ferrophosphorus slag to the alkaline liquid is 1:3-10, preferably 1:4-6; Preferably, in step (a), the mass fraction of the alkaline liquid is between 8% and 20%; Preferably, in step (a), the alkaline liquid comprises a sodium hydroxide solution and / or a potassium hydroxide solution; Preferably, in step (a), during the reaction of the iron phosphorus slag with the alkaline liquid, the temperature of the mixture is 30-80°C, and the reaction time is 1-3 hours.

3. In step (a), the acid used in the acid solution includes at least one of sulfuric acid, hydrochloric acid, phosphoric acid, and nitric acid, and is preferably phosphoric acid; Preferably, in step (a), the mass fraction of the acid solution is between 30% and 85%; The method for producing iron phosphate using iron phosphorus slag according to claim 1, wherein in step (a), the acid solution is added until the pH of the mixture is 5.0 to 7.5, more preferably 6.8 to 7.

1.

4. In step (b), the molar ratio of iron element in the filter cake to hydrogen ions in the acid solution is 1:3.1-4; Preferably, in step (b), the acid comprises at least one of sulfuric acid, hydrochloric acid, nitric acid and phosphoric acid; Preferably, in step (b), the molality of the acid solution is 1 to 3 mol / kg; Preferably, in step (b), the temperature of the mixture during the decarbonization reaction is 60 to 80° C.; The method for producing iron phosphate using the iron phosphorus slag according to claim 1, wherein in step (b), the decarbonization reaction time is 1 to 3 hours, and more preferably 1 to 1.5 hours.

5. In step (c), the temperature of the mixture during the titanium removal and copper removal reaction is 75 to 85° C.; Preferably, in step (c), the solid-liquid separation is performed when the pH of the mixture during the titanization and copper removal reaction reaches 2 to 4.

2. The method for producing iron phosphate using the iron phosphorus slag according to claim 1.

6. In step (d), the oxidizing agent includes at least one of hydrogen peroxide, sodium peroxide, potassium peroxide, sodium persulfate, ammonium persulfate, and potassium persulfate; Preferably, in step (d), the molar ratio of ferrous ions in the fourth filtrate to hydrogen peroxide in the hydrogen peroxide solution is 1:0.55-0.

75. The method for producing iron phosphate using iron phosphorus slag according to claim 1.

7. The method for producing iron phosphate using the iron phosphorus slag according to claim 1, wherein in step (d), the molar ratio of the phosphate ions in the second filtrate to the ferrous ions in the fourth filtrate is 1.05 to 1.5:

1.

8. In step (d), the temperature of the mixture during the reaction is 80-95° C.; Preferably, in step (d), the reaction time is between 2 and 6 hours; Preferably, in step (d), the sintering temperature is 550 to 700° C., the method for producing iron phosphate using iron phosphorus slag according to claim 1.

9. Produced by a method for producing iron phosphate using the iron phosphorus slag according to any one of claims 1 to 8, Preferably, said iron phosphate has an iron / phosphorus ratio of 0.96 to 0.

98.

10. A positive electrode material for a lithium ion battery, comprising the iron phosphate according to claim 9.

Citation Information

Patent Citations

  • Preparation method of battery grade iron phosphate with low impurity, high iron-phosphorus ratio and large specific surface

    CN108455547A

  • Recovery method of ferrophosphorus slag after lithium extraction from lithium iron phosphate

    CN112551498A

  • Method for recovering lithium from waste lithium iron phosphate battery and preparing iron phosphate

    CN113061723A

  • Method for recycling positive electrode material of waste lithium iron phosphate battery

    CN113735087A

Cited By

  • A method for producing lithium iron phosphate from waste lithium iron phosphate material.

    JP2026109503A